Application of Cause-and-Effect-Analysis for Evaluating Causes of Fire Disasters in Public and Private Secondary Schools in Ilorin Metropolis, Nigeria - , Alade E. Ilori; , Bulus A. Sawa; , Abdullahi A. Gobir (Archives of Current Research International, 2020)
The contributions of fire disaster to the varying degrees of students’, staff and schools’ property and/or lives lost in secondary schools in Nigeria is recently alarming. The study assessed causes of fire disaster in public and private secondary schools in Ilorin metropolis, Nigeria. The objectives were to identify latent causes of fire disaster, use the fishbone diagram to illustrate and analyze the root-causes of fire disaster in secondary schools. The exploratory research strategy was used. The target population was 18 senior public and private secondary schools, Ilorin having 18 principals, 965 teachers and 3765 senior secondary 2 students. From the target population, simple random sampling technique through a pick and not-return balloting was employed to sample 72.22% of the principals, 14.8% each of the teachers and students. Data were collected through in-depth interviews, questionnaire, participatory observation, and were analyzed using cause-and-effects-analysis. The findings reveal fire disasters in public and private secondary schools in Ilorin metropolis are primarily caused by bush/waste burning, electrical fault/wiring, arson, carelessness, and alcohol, smoking. Results also showed that the root-causes of fire phenomenon from the classic categories were setting undergrowth on fire, non-insulated wiring system and sparks from wrong connections, emotional induced from cultism rivalry among male teachers and students over a girl and superiority within and outside the school, mishandling of chemicals in various laboratories during experimentation, and lack of proper fencing of school compound. The study recommends that schools in the metropolis should prepare and anticipate future fire tragedy. Consequently, since there are several factors responsible for fire incidents, further studies could be conducted to clarify the sequence or magnitude of each cause of the fire outbreak.